PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT ISLAM AT-TAQWA GUMAWANG - Fitra Margaret (STIE DWI SAKTI BATURAJA, 2017)
This research is eksplanasi research using sample 20% from population that is 40 responden. Using simple random sampling method. Data analysis method used is descriptive analysis method percentage, multiple correlation coefficient and multiple linear regression analysis. Technique of data and research test using classical assumption test, multicollinearity test, heteroscedasticity test. Using multiple correlation coefficients to know the relationship of variables X and Y variable simultaneously of 0.525 or 52%, using SPSS 16 obtained multiple regression equation Y = 22.324 + 0.349X1 + 0.239X2. Partial test results obtained t arithmetic 1.968 < t table 2.026 significance 0.057 > 0.05 means H1 rejected, work discipline obtained t arithmetic 1.755 < t table 2.026 significance 0.088 > 0.05 means H2 rejected. F test results show F calculate 7.050> F table 3.25 with significance value = 0.003 <0.05 which means H3 accepted.